The Study of Discourse on Digital Pathology and Spiritual Education - Subhan Fadli; Zain Sartono (Green Publisher Indonesia, 2023)
Pathological behavior is any form of behavior considered by most citizens of society as disturbing, undesirable, harmful, and detrimental to public because it violates community customs (and these customs are necessary to ensure the prosperity of living together). Digital pathology is different from the disciplines of Islamic morality or moral science. If it is moral science, it is a discipline that discusses the ideal form of Muslim personality and strives so that this ideal can be applied in the real life of a Muslim, while digital pathology is a discipline that focuses on examining the non-ideal/negative form of child/adolescent personality and seeks to overcome it. This study aims to present a discourse on digital pathology and spiritual education discourse to obtain a definitive formulation of digital pathology and spiritual education and affirm the concept of spiritual education that is relevant to this researcher. This study, begins by expressing anthropocentric, sociological, and theocentric views on spiritual education and digital pathology and their dimensional dimensions. This study uses a qualitative method. Qualitative research is an umbrella concept that includes several research formats that will help understand and explain the meaning of social phenomena from existing natural settings. Overcoming digital pathology through Qur'an-based spiritual education is a conscious effort in overcoming and preventing diseases caused by devices, namely various social and individual crises that include identity crises, legality, penetration, participation, distribution and moral crises.